PEMBIAYAAN USAHA MIKRO KECIL DAN MENENGAH: ANALISIS DI BANK SYARIAH INDONESIA KCP MUARA BULIAN - Erwin Saputra Siregar; Suchi Soumi Shinta; Abd Malik (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2021)
This research aims to determine the role of Islamic banking financing in improving the ummah's economic level, including MSME financing, and the obstacles faced by MSMEs in the micro-business financing application process. This type of research is qualitative, with data collection techniques through interviews, observations, and documentation. The result of this research is that the financing of Islamic banking micro-businesses against MSMEs is carried out by providing a form of services in the form of microfinance to customers who have been recorded at Bank Syariah Indonesia of Muara Bulian, then continued with the stages of training and extension activities facilitated directly by Islamic banks. The obstacles customers face when applying for microfinance are the number of customers who have not met the technical requirements of Islamic banking, such as limited guarantees and income that fluctuates, resulting in the emergence of problematic financing.